Prominent protumoral cellular compartments of the tumor microenvironment in triple-negative breast cancer - Sun, Shuai; Zhao, Pan; Wang, Changrong; Du, Junjun; Zhang, Tingting; He, Xiangyun; Zuo, Zhibo; Li, Nan; Zhou, Rongjing (Frontiers in Cell and Developmental Biology, 2026)
Triple-negative breast cancer (TNBC) is a highly aggressive subtype of breast cancer characterized by the absence of estrogen, progesterone, and HER2 receptor expression. This malignancy is often associated with a poor prognosis, early recurrence, and limited treatment options. The tumor microenvironment (TME) in TNBC plays a pivotal role in tumor progression, immune evasion, and therapeutic resistance. In recent years, an increasing body of evidence has highlighted the critical interactions between cancer cells and the components within the TME, including immune cells and soluble components. These interactions influence not only the biological behavior of the tumor but also its response to treatment. Exploring the complex interplay between tumor cells and immune components continues to inform the development of more effective therapeutic approaches. In this study, we provide a synopsis of advancements regarding the TME in TNBC. In light of different cellular compartments, we delineate multiscale interplays within the stroma–tumor symbiosis and highlight their antitumor functions and promising targeting strategies.